A high capacity thiospinel cathode for Mg batteries. Issue 7 (3rd June 2016) - Sun, Xiaoqi; Bonnick, Patrick; Duffort, Victor; Liu, Miao; Rong, Ziqin; Persson, Kristin A.; Ceder, Gerbrand; Nazar, Linda F.
Abstract : A Mg full cell with a thiospinel cathode material shows 190 mA h g −1 capacity and relatively stable capacity retention. Abstract : Magnesium batteries are energy storage systems that potentially offer high energy density owing to their ability to employ magnesium metal as a negative electrode. Their development, however, has been thwarted by a paucity of functional positive electrode materials after the seminal discovery of the Mo6 S8 Chevrel phase over 15 years ago. Herein, we report the second such material – a thiospinel – and demonstrate fully reversible Mg 2+ electrochemical cycling vs. a Mg anode, which is complemented by diffraction and first principles calculations. The capacity approaches 80% of the theoretical value at a practical rate (C/5) at 60 °C, and yields a specific energy of 230 Wh kg −1, twice that of the Chevrel benchmark. Our results emphasize the advantage in employing "soft" anions to achieve practical divalent cation mobility.